The National Socialist programme of sport, physical education and recreation and that of the German Democratic Republic - Carr, Gerald A.(Gerald Anthony),1936- (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1972.